Efficacy of Aloe vera in post-exodontia tissue response in incisors from Cavia porcellus - Vadillo Palacios, Grisel Yulliana (2019)
Introduction: In the field of medicinal plants and their benefits on oral health, research on Aloe vera is found, however, these are mainly developed in the observation on inflammation and not in the whole process of alveolar healing. As a result, this quasi-experimental and longitudinal study was performed. Objective: To determine the tissue response of alveoli in Cavia porcellus mandibular incisors after intra-alveolar application of Aloe vera. Materials and Methods: Twenty-four animals were selected and divided into 2 groups (experimental and control group). The evolution of the tissue response was evaluated in periods of 24 hours, 7 and 14 days in each group. Results: Several results were obtained in each period, with an improvement in the reaction phases of inflammatory cells and granulation, otherwise in the phases of epithelialization and osteogenesis. Conclusion: The Aloe vera has a positive but statistically non-significant effect proving its usefulness for healing in this type of wound so characteristic in the field of dentistry.